Analisis Analisis Kendala Penerapan Zakat Digital Pada BAZNAS Kota Malang: Analisis Kendala Penerapan Zakat Digital Pada BAZNAS Kota Malang - Eva, Yohana (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2023)
Since 2016 BAZNAS has developed a digitalization strategy in zakat payments. Since pandemic BAZNAS has maximized zakat management through digitalization techniques. This is in accordance with the regulation of the Ministry of Religion Number 6 of 2020 which orders that the management of zakat is minimally possible through physical contact. Digitalization has begun to be maximized, however, until now digitization has not been fully carried out simultaneously and evenly. BAZNAS Malang City is one of the BAZNAS that has developed the concept of digitizing zakat, however, zakat management at BAZNAS Malang City has not fully implemented the digital concept. Therefore, to find out what causes BAZNAS in Malang City to not fully implement digital zakat, this article was prepared to analyze the obstacles to implementing digital zakat at BAZNAS Malang City. This article was compiled using a descriptive qualitative approach using a case study strategy in problem analysis. This study uses primary data and secondary data, primary data obtained through structured interviews with BAZNAS officers in Malang City and secondary data obtained from related literature articles. Based on the results of research on collecting zakat, infaq, shadaqah funds at BAZNAS Malang City using cash and digital methods. In the distribution of funds, they still use traditional methods, however, BAZNAS Malang City in reporting has partially used digital techniques.